Taxonomic revision and cladistic analysis of the Neotropical genus Acrochaeta Wiedemann, 1830 (Diptera: Stratiomyidae: Sarginae) - Fachin, Diego Aguilar; Amorim, Dalton De Souza (Zootaxa, 2015)
The Neotropical genus Acrochaeta Wiedemann is revised and a cladistics analysis of the genus based on morphological characters is presented. This paper raises the total number of extant Acrochaeta species from 10 to 14 with the description of nine new species, the synonymy of one species, the transfer of five species to other genera and the transfer of one species of Merosargus to Acrochaeta. The new species described (of which eight are from Brazil and one from Bolivia and Peru) are Acrochaeta asapha nov. sp., A. balbii nov. sp., A. dichrostyla nov. sp., A. polychaeta nov. sp., A. pseudofasciata nov. sp., A. pseudopolychaeta nov. sp., A. rhombostyla nov. sp. A. ruschii nov. sp. and A. stigmata nov. sp. The primary types of all Acrochaeta species were studied at least from photos, when possible with the study of dissected male or female terminalia. A. mexicana Lindner is proposed as a junior synonym of A. flaveola Bigot. M. chalconota (Brauer) comb. nov., M. degenerata (Lindner) comb. nov., M. longiventris (Enderlein) comb. nov. and M. picta (Brauer) comb. nov. are herein transferred from Acrochaeta to Merosargus Loew, and Chrysochlorina elegans (Perty) comb. nov. is transferred from Acrochaeta to Chrysochlorina James. A. convexifrons (McFadden) comb. nov. is transferred from Merosargus to Acrochaeta. The limits of the genus and its insertion in the Sarginae are considered, and an updated generic diagnosis is provided. All species of the genus are redescribed and diagnosed, and illustrated with photos of the habitus, thorax, wing, and drawings of the antenna and male and female terminalia. Distribution maps are provided for the species, along with an identification key for adults of all species. Parsimony analyses were carried out under equal and implied weight. Our matrix includes 43 terminal taxa—of which 26 are outgroup species from four different sargine genera—and 59 adult morphological characters. The phylogenetic analysis supports the monophyly of Acrochaeta based on features of the head, thorax and abdomen. An inner clade (Acrochaeta flaveola species group) within the genus was clearly recovered based on characters of male and female terminalia. There is good evidence for the paraphyly of Merosargus with Acrochaeta as a subclade, demanding a wider study of the subfamily for a sound solution for the genus Merosargus.